A pesquisa brasileira em educação musical infantil: tendências teórico-metodológicas e perspectivas - Nieri, Debora [UNESP] (2014)
This research refers to the field of children’s musical education, giving emphasis to the relationship among education, music and childhood. It is recognized as a bibliographic theoretical study, which mainly analyzes theses and academic paperwork production, under a critical manner, in the period between 1996 and 2012, originated from postgraduation courses at Brazilian universities, concerning musical education directed to children from 0 to 6 years old in Brazil, collected in the Bank of Theses of CAPES and in the websites of Post-Graduation Programs (PPG in Portuguese) in Music and Education. The target is mapping this field with the aim to document it, taking into account the Gamboa methodological perspective (1987) of the technical, thematic and theoretical level viewpoints, and observe possible streamlines and perspectives arising from international literature, together with a study on articles in Newspapers and International Periodicals considered relevant to the Music Educational area. Field variability and different viewpoints and bonds that researchers establish with the object and focus on the research are also emphasized. The socialization of this knowledge can exploit the State and society in the elaboration and orientation of public policies, implementation and evaluation of educational programs in the specific field of children’s musical education